Phytoremediation of domestic wastewater by azolla in a constructed wetland / Redzaniell Afiq Mohd Rosdi - Redzaniell Afiq, Mohd Rosdi (2022)
One of the major environmental problems in the present scenario is water pollution. Increased population and industrialization fasten the water pollution rate. Increase in population leads to high domestic water consumption and domestic wastewater production which plays an important role in polluting water resources. In this study an attempt is made to evaluate effectiveness of phytoremediation technique using Azolla fern (Azolla pinnata) for domestic wastewater by constructed wetland units. Parameters like pH, Biochemical oxygen demand (BOD), Chemical oxygen demand (COD), Ammoniacal nitrogen (NH3-N), Phosphate (PO43-), were analyzed for sample after 7 days of phytoremediation within 49 days of detention period. Constructed wetlands using Azolla fern observed with a high removal efficiency in all tested parameters except pH. Concentration of BOD, COD, NH3-N and PO43- reduced from 27.4 mg/L, 132 mg/L, 3.28 mg/L, 3.42 mg/L to 13.8 mg/L, 9 mg/L, 0.08 mg/L, 0.09 mg/L respectively whereas the pH increase from 6.60 to 7.9. The removal efficiency % BOD (49.64%), COD (93.18%), NH3-N (97.56%) and PO43- (97.37%). The study conducted by Neethu & Chinamma (2017), indicated that after 28 days of treatment the removal efficiency % BOD (89.61%), COD (92.41%), NH3-N (91.12%) and PO43- (94.93%). For future study, it would be recommended to apply appropriate constructed wetland design, implement odour reduction strategies, select suitable plant and determine amount of dissolved oxygen.